Public administration evolving : from foundations to the future - Guy, Mary E.; Rubin, Marilyn M. (London, United Kingdom : Routledge Taylor & Francis Group, 2015)
"Public Administration Evolving: From Foundations to the Future demonstrates how the theory and practice of public administration has evolved since the early decades of the twentieth century. Each chapter approaches the field from a unique perspective and describes the seminal events that have been influential in shaping its evolution. This book presents major trends in theory and practice in the field, provides an overview of its intellectual development, and demonstrates how it has professionalized. The range from modernism to metamodernism is reflected from the perspective of accomplished scholars in the field, each of whom captures the history, environment, and development of a particular dimension of public administration. Taken together, the chapters leave us with an understanding of where we are today and a grounding for forecasting the future"-
The Public Context / David H. Rosenbloom -- From Intergovernmental to Intersectoral / Donald F. Kettl -- From Trust to Doubt : The Federal Government's Tough Challenges / Chester A. Newland -- From Local to Global / Donald E. Klingner -- From Silos to Networks : Hierarchy to Heterarchy / Rosemary O'Leary -- From Administration to Management / Kaifeng Yang -- From Outputs to Outcomes / Kathryn E. Newcomer -- From Paper to Cloud / Jooho Lee and B.J. Reed -- From Sameness to Differentness / Norma M. Riccucci -- From Equality to Social Equality / Susan T. Gooden -- Seventy-Five Years of Professionalization / Jeremy F. Plant -- From Ethical Expectations to Professional Standards / James H. Svara -- Looking Back, Moving Forward / Mary E. Guy and Marilyn M. Rubin.
Includes bibliographical references and index.
Keywords: PUBLIC ADMINISTRATION -- PHILOSOPHY